Energy and water use by invasive goats (Capra hircus) in an Australian rangeland, and a caution against using broad-scale allometry to predict species-specific requirements - Munn, A.; Cooper, Christine; Russell, B.; Dawson, T.; McLeod, S.; Maloney, S. (Elsevier Inc., 2012)
Feral goats (Capra hircus) are ubiquitous across much of Australia's arid and semi-arid rangelands, where they compete with domestic stock, contribute to grazing pressure on fragile ecosystems, and have been implicated in the decline of several native marsupial herbivores. Understanding the success of feral goats in Australia may provide insights into management strategies for this and other invasive herbivores. It has been suggested that frugal use of energy and water contributes to the success of feral goats in Australia, but data on the energy and water use of free-ranging animals are lacking. We measured the field metabolic rate and water turnover rate of pregnant and non-pregnant feral goats in an Australian rangeland during late summer (dry season). Field metabolic rate of pregnant goats (601 ± 37 kJ kg− 0.73 d− 1) was 1.3 times that of non-pregnant goats (456 ± 24 kJ kg− 0.73 d− 1). The water turnover rate of pregnant goats (228 ± 18 mL kg− 0.79 d− 1) was also 1.3 times that of non-pregnant goats (173 ± 18 kg− 0.79 d− 1), but the difference was not significant (P = 0.07).There was no significant difference in estimated dry matter digestibility between pregnant and non-pregnant goats (mean ca. 58%), blood or urine osmolality, or urine electrolyte concentrations, indicating they were probably eating similar diets and were able to maintain osmohomeostasis. Overall, the metabolic and hygric physiology of non-pregnant goats conformed statistically to the predictions for non-marine, non-reproductive placental mammals according to both conventional and phylogenetically independent analyses. That was despite the field metabolic rate and estimated dry matter intake of non-pregnant goats being only 60% of the predicted level. We suggest that general allometric analyses predict the range of adaptive possibilities for mammals, but that specific adaptations, as present in goats, result in ecologically significant departures from the average allometric curve. In the case of goats in the arid Australian rangelands, predictions from the allometric regression would overestimate their grazing pressure by about 40% with implications for the predicted impact on their local ecology.